2022
DOI: 10.1002/ejoc.202200220
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzothiazepine Based MCR Chemistry

Abstract: Privileged scaffolds which can unveil unknown territories of the chemical space are constantly prominent. As such, 1,5-dibenzothiazepines not only offer structural diversification but also a very unique binding mode due to their "butterfly" conformation. We provide MCR-based annulations of this scaffold towards three different tetracycles in a straightforward, two-step procedure. We synthesize a library of 30 tetracyclic 1,5tetrazolo-, fused imidazo-and lactam-1,5-dibenzothiazepines with scalable and one-pot p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…18 a Path B starts with the nucleophilic attack of isocyanides on cyclic imines 1 , and zwitterionic intermediate II is formed. 24 Then, intermediate III is produced by increasing the amine nucleophilicity of zwitterionic intermediate II to acetylenedicarboxylate 3 . Finally, pyrrole-fused dibenzoxazepine 4 is obtained by sequential processes involving an intramolecular cyclization/[1,3]- H shift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 a Path B starts with the nucleophilic attack of isocyanides on cyclic imines 1 , and zwitterionic intermediate II is formed. 24 Then, intermediate III is produced by increasing the amine nucleophilicity of zwitterionic intermediate II to acetylenedicarboxylate 3 . Finally, pyrrole-fused dibenzoxazepine 4 is obtained by sequential processes involving an intramolecular cyclization/[1,3]- H shift.…”
Section: Resultsmentioning
confidence: 99%
“…16 In particular, the cyclic imines derived from dibenzoxazepine and dibenzothiazepine are used in many reactions owing to their wide range of applications and biological properties. 17 In order to examine the reaction behavior of these dibenzoxazepine imines and based on our previous reports, 5,13 we tried to convert these compounds to the respective pyrrole-fused dibenzoxazepines III with the aid of the PJU-3CR (Scheme 1c). However, as reported in this paper, we observed that under the reaction conditions mentioned above, the dibenzoxazepine imines react contrary to our expectations and convert to pyrrole-fused dibenzoxazepines IV (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…It does, however, require a relatively long reaction time and reflux temperature. [81] These issues could be resolved by employing microwave irradiation (Figure 26 , entry b ) which proved to be efficient and applicable to all four 2‐halobenzaldehydes as well as substituted 2‐chloro‐ or 2‐fluorobenzaldehydes 84 . The reactivity seemed to decrease in the following order: F>Cl>Br>I, which could be explained by increasing size of the atom and decreasing electronegativity.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…The reaction was easy to perform, used environmentally friendly reaction conditions, only took ten minutes and proved easy to purify [83] . Other possible strategies for diversification, including MCRs, encompass the Ugi tetrazole, [81] Castagnoli–Cushman, [81] Mannich, [85] aza‐Henry, [86] Strecker [87] and Pudovic reaction [88] . More detailed information on the various synthetic methods for 1,5‐dibenzothiazepines can be found in the literature [3,89] …”
Section: Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation